1994
DOI: 10.1055/s-2007-1001682
|View full text |Cite
|
Sign up to set email alerts
|

Rat Liver Injury Induced by Hypoxic Ischemia and Reperfusion: Protective Action by Somatostatins is Independent from Changes in Glucose Metabolism

Abstract: Changes in glucose metabolism mediated by natural somatostatin and two derivatives (octreotide, 008) were studied in hypoxic ischemic cell injury of the isolated perfused rat liver. The tested somatostatin and its analogues were previously shown to exert protective actions in liver damage induced by hypoxic ischemia and reperfusion. In isolated perfused livers of rats starved for 24 hours and unstarved rats flow rate was reduced and oxygen supply interrupted for 180 min. Then the livers were normoxically reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Next, we used these NO-sensing probes to investigate the anti-HIRI behavior of octreotide (Oct), which is a synthetic somatostatin octapeptide that primarily inhibits the secretion of growth hormone . Recent studies have demonstrated that Oct can reduce HIRI significantly, possibly via elevation of NO concentrations, although a detailed mechanism remains unclear. Hepatic ischemia reperfusion surgery was performed on rat models with/without octreotide (Oct) pretreatment, and NO levels in the serum and liver tissue samples were monitored.…”
mentioning
confidence: 99%
“…Next, we used these NO-sensing probes to investigate the anti-HIRI behavior of octreotide (Oct), which is a synthetic somatostatin octapeptide that primarily inhibits the secretion of growth hormone . Recent studies have demonstrated that Oct can reduce HIRI significantly, possibly via elevation of NO concentrations, although a detailed mechanism remains unclear. Hepatic ischemia reperfusion surgery was performed on rat models with/without octreotide (Oct) pretreatment, and NO levels in the serum and liver tissue samples were monitored.…”
mentioning
confidence: 99%
“…HI is a temporary inflow and/or outflow blockage via vascular clamping to decrease intraoperative blood loss, which can cause apoptosis of liver cells and lead to injury of the liver . Oct is a synthetic somatostatin octapeptide whose primary role is to inhibit the secretion of growth hormone, but has been found to significantly reduce hepatic ischemia-reperfusion injury (HIRI) through a mechanism that remains unclear. Accordingly, herein, through the measurement of liver hypoxia by using the prepared ratiometric SERS nanosensor, we examine whether hepatic ischemia can generate a hypoxic environment.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a decrease in the serum concentrations of glucose in both, the IR and HGIR groups compared to SH. It has been demonstrated that liver ischemia impairs glucose metabolism, affecting the gluconeogenesis pathway and decreasing the serum glucose concentration during the late ischemia and reperfusion (Bailey & Reinke 2000;Bloechle et al 1994). There was no significant increase, but a trend, in the serum activity of ALP and the serum concentration of total bilirubin after the induction of IR injury, indicating that IR injury induction affected to a lesser extent the bile ducts than the liver parenchyma.…”
Section: Discussionmentioning
confidence: 98%